Identification of Local Wisdom of The Sasak Tribe In Chemistry Learning as an Effort to Strengthen Student Character - Ratna Azizah Mashami; Suryati Suryati; Baiq Muli Harisanti; Yusran Khery (Jurnal Penelitian Pendidikan IPA, 2023)
Globalization has a negative impact on local wisdom and the character of the successor of the Indonesian nation. It causes the culture of other countries to influence local wisdom so that it experiences a shift and slowly disappears. It triggers youth violence and erodes morals, character, sense of humanity, and nationalism. Students who are dominated by the Sasak tribe are currently less familiar with their traditions and culture. The solution to this problem is to integrate local wisdom into formal chemistry learning. This study aims to identify local wisdom of the Sasak tribe that can be integrated in chemistry learning. The approach used in this research is qualitative. The research sample is cultural practitioners and the Sasak people. Sampling using purposive technique. The implementation of this research consists of four stages based on data analysis of the Miles and Huberman Model, namely data collection, data reduction, data presentation, and drawing conclusions. The data collection technique is triangulation, which combines interviews, observations, and documents. The results of this study are local wisdom of the Sasak tribe that can be integrated in chemistry learning. The local wisdom includes mopping with cow dung, dilah jojor, nyesek, and gendang beleq. The results of the analysis of local wisdom show that there is relevance to chemistry, namely the concepts of organic compounds, inorganic compounds, chemical bonds, elemental chemistry, instrument analysis, chemical separation, and chemistry of natural materials. The integration of local wisdom into chemistry learning has an impact on maintaining the existence of local wisdom of the Sasak tribe as well as strengthening the character of students